Tissue Depletion of Olaquindox and Its Six Metabolites in Pigs and Broilers: Identification of a Suitable Marker Residue - Zhang, Heying; Qu, Wei; Ding, Chaoyue; Han, Juncheng; Xie, Shuyu; Liu, Zhenli; Huang, Lingli; Pan, Yuanhu; Yuan, Zonghui (Frontiers in Veterinary Science, 2021)
The depletion profiles of olaquindox and its six major metabolites, including O1 (N1-deoxyolaquindox), O2 (Deoxyolaquindox), O3 (2-carboxamide-3-methylquinoxaline-N4-oxide), O4 (2-carboxymethylaminocarbonyl-3-methylquinoxaline-N4-oxide), O5 (2-carboxymethylaminocarbonyl-3-methylquinoxaline), and O6 (3-methyl-quinoxaline-2-carboxylic acid, MQCA) were studied with a sensitive and accurate HPLC-UV method in pigs and broilers after oral administration of olaquindox at rate of 50 mg kg−1 feed for 14 consecutive days. Five medicated pigs and six medicated broilers and one control animal were anesthetized and sacrificed at different time points (6 h, 1, 3, 7, and 14 days for pigs and 6 h, 1, 3, 5, and 7 days for broilers) after the cessation of the treatment and samples of muscle, liver, kidney and fat were collected. The samples were assayed using a liquid chromatographic method. The mean concentrations of deoxyolaquindox residues in all tissues of pigs were higher than other residues at each time point. MQCA was detected at lower levels and eliminated more rapidly than deoxyolaquindox (calculated t1/2 1.78d - 2.28d vs. t1/2 2.04d - 2.46d). The elimination half-lives of deoxyolaquindox residue in broilers liver and kidney tissues (t1/2 > 4d) were much longer than that in pigs, so the use of olaquindox in poultry is clearly inappropriate, for significant drug residues will occur. The results that deoxyolaquindox occurs at higher concentrations in kidney tissue and is more persistent than other residues in the edible tissues of pigs indicate that deoxyolaquindox is the most relevant marker residue and should be monitored in the routine surveillance of olaquindox related residues in the food of animal origin.